ADHERENCE TO THE WHO GUIDELINES OF MANAGEMENT OF SEVERE ACUTE MALNUTRITION IN CHILDREN 6 MONTHS TO 5 YEARS - MUSHTAQ, K; MUSHTAQ, A; YAQOOB, Z; HANIF, I (Biological and Clinical Sciences Research Journal, 2022)
To evaluate the management of severe acute malnutrition according to WHO guidelines in children. A prospective study was conducted at Paediatrics Department of Mother and Children Complex DHQ Hospital Sheikhupura from August 2021- August 2022. A total of 200 children with age range between 6 months and 5 years were included in the study. Personal information of patients was supposed to be recorded along with malnutrition classification, diagnostic signs, treatment and its outcomes according to the WHO guidelines. All the data was assessed by SPSS version 22. The staff did not record complete information such as family history, health condition of the child, and diagnostic signs. The weight for height Z score was calculated in all patients (100%). The classification of malnutrition was also not in adherence with WHO i.e seven types were recorded instead of two. Laboratory tests other than blood film , blood sugar and hemoglobin concentrations were not performed in any of the children. 82 (41%) children received intravenous dextrose. Rehydration solution for malnutrition was not administered to any of the children. Poor adherence to WHO guidelines regarding severe acute malnutrition was observed in children younger than 5.